PENINGKATAN KEMAMPUAN MENULIS CERPEN MELALUI METODE OUTING CLASS PADA SISWA KELAS V MADRASAH IBTIDAIYAH - Hannan Marwi, Zul; Siregar, Nasyariah; Saputri, Vioni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low short-story writing ability of fifth-grade students at MI Rahmatullah, Jambi City. Students experienced difficulties in determining themes, developing characters and characterization, organizing plots, determining settings, and conveying messages. This study aimed to improve students' short-story writing ability through the implementation of the Outing Class method. The study employed Classroom Action Research using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. The research involved 20 fifth-grade students and was conducted in two cycles. Data were collected through writing tests, observations, interviews, and documentation. Students' writing ability was assessed using five indicators: theme, characters and characterization, plot, setting, and message. The results showed a gradual improvement. In the pre-cycle, the total score was 1,350, the mean score was 67.50, and learning mastery was 30% (6 students). In Cycle I, the total score increased to 1,485, the mean score to 74.25, and mastery to 50% (10 students). In Cycle II, the total score increased to 1,585, the mean score to 79.25, and mastery reached 85% (17 students). Teacher activity increased from 55% in Cycle I to 95% in Cycle II, while student activity also improved. These findings indicate that the Outing Class method provides direct learning experiences that help students generate ideas, develop story elements, and transform observations into short stories. Therefore, Outing Class can be used as an alternative method for improving short-story writing ability in elementary and madrasah education.